Decision making in neurovascular disease - Rangel-Castilla, Leonardo; Nakaji, Peter; Siddiqui, Adnan H.; Spetzler, Robert F. (Robert Friedrich), 1944-; Levy, Elad I. (Thieme, 2018)
Neurovascular medicine has emerged as an established, semi-independent subspecialty of neurology and neurosurgery. Decision Making in Neurovascular Disease focuses on the challenging process of determining the best approach for managing patients with intracranial atherosclerosis, carotid artery disease, stroke, aneurysms, arteriovenous malformations, arteriovenous fistulae, cavernous malformations, and hypervascular tumors. Leonardo Rangel-Castilla, Robert Spetzler, esteemed coauthors, and an impressive cadre of experts discuss highly divergent modalities including medical management, open cer.